Manizales City: A Smart City? - Arias Valencia, Laura Manuela; Ramirez Castañeda, Luz Arabany (Journal of Sociocybernetics, 2018)
The use in the cities of Information and Communications Technologies (ICT) has increased, due to the political and economical control, that has favored their development. This new type of city (system) holds different names: Digital City and Smart City. The Smart City is a self-sustaining city. In the most innovative-technological dimension, there are included the factors for sustainable development. The Smart City uses the ICT, with the purpose of providing an infrastructure, that can guarantee: a sustainable development, an better life quality for its population, a higher efficiency when using the resources that are available and, a more active participation of the citizens. The focus of Smart City, is more popular among projects that imply transformation for this kind of cities. However, in researches that measure and classify some of the smart cities, there have been presented ideal models, where the main characteristics are based in the subsystems of these cities. The factor that allows establishing the level of intelligence that a city has achieved, is the analysis of a real city and then, comparing it to the features of a Smart City. This measurement model, can be adopted by the municipal government of the city, in order to carry out special improvement activities in their development plans. The case in this paper is the city of Manizales, which is considered to be the ICT city of Colombia. It was labeled as a Smart City by the adoption of intensive systems in ICT. Nevertheless, and according to a recent study in FEDESARROLLO, Manizales has the lowest usage rate of ICT in Colombia, based on the different components of urban intelligence. Therefore, this label is not based in a measurement that comprises all of the factors that define this type of cities. The project that is presented in this paper aims to set an assessment model, in order to measure the intelligence of Manizales as a Smart City. This paper is the final paper for graduation, in the Masters Program of Information Systems Management (Major).